Labor migration and minority group empowerment The Nikkeijin in Davao and their association - Fresnoza-Flot, Asuncion (Asian Studies, 2008)
After World War II, Filipino Nikkeijin suffered social and economic difficulties. As a result, they tried to conceal their Japanese origin to escape reproaches and teasing. Their shared experience of social discrimination mobilized them into associations that helped them to socially empower themselves. To explore the process of their empowerment, the present study examines the case of Davao Nikkeijin and their association, Philippine Nikkeijin Kai Inc. (PNJK). Looking at the different dimensions of empowerment, it shows how this association has helped some Nikkeijin acquire Japanese nationality and/or migrate to Japan to work there. Nowadays, Nikkeijin have good socio-economic status in the Philippines and are not a marginalized minority group anymore.